Media psychology - BREWER, Gayle (ed.); Brewer, Gayle, 1978- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2011)
"This edited textbook brings together broad and cutting-edge coverage of the core areas in media psychology for undergraduate, introductory-level students. Covering persuasion and influence, interaction with the media, and representation, the authors draw on specific campaigns and studies to introduce readers to key issues in this fascinating field"--
Includes bibliographical references (p. 229-272) and index.
Keywords: Mass media -- Psychological aspects; PSYCHOLOGY / Social Psychology; SOCIAL SCIENCE / Media Studies; PSYCHOLOGY / Applied Psychology; LANGUAGE ARTS & DISCIPLINES / Communication Studies